IMPLIKASI PERAN GANDA PEREMPUAN DALAM KEHIDUPAN KELUARGA DAN LINGKUNGAN MASYARAKAT - Ramadhani, Ninin (Universitas Pendidikan Indonesia, 2016)
This research background is about the double role of a woman who make batik that must be smart to devided her time for her family, works and also a part of society. This research use description of qualitative approach. The data was collected by observation, depth interview and documentation of studi. The finding result of this research are: (1) the general illustration of double role woman who makes batik as a housekeeper, as makes batik, as a member of PKK and a part of Majelis Ta'lim. (2) there are two part problem which is come to woman who makes batik, internal and external. For instance the problem based on internal such as feel tired, feel bored and the problem from external is limited of time. (3) there are positive and negative impact for woman who makes batik. The advantages to woman who make batik, it can helpful her family.